Deaths and parasuicides associated with mefloquine chemoprophylaxis: A systematic review. Issue 20 (November 2017) - Tickell-Painter, Maya; Saunders, Rachel; Maayan, Nicola; Lutje, Vittoria; Mateo-Urdiales, Alberto; Garner, Paul
Abstract: Background: Mefloquine is recommended in international health guidelines for preventing malaria in travellers. Reports of psychosis and suicide are often alluded to but are not clearly established. Methods: We carried out a systematic review of the literature to identify and critically appraise any reported death or parasuicide associated with mefloquine prophylaxis. We developed a comprehensive search that included publications up to 11 July 2017. We included case studies but excluded newspaper reports. Two authors independently appraised each death or parasuicide against a standardised causality assessment tool. The protocol was registered on PROSPERO (CRD42016041988). Results: We identified 527 articles that required full-text retrieval; of these 17 were unique publications that reported deaths or parasuicide. Eight unique publications had sufficient detail to be included in causality assessment. We identified 2 deaths with a probable association that appeared to be idiosyncratic drug reactions; we categorised the remaining 8 deaths as "unlikely" to be related to mefloquine, or "unclassifiable". There was one parasuicide with a possible causal association. There were 9 additional publications that searched spontaneous drug reporting databases; none provided sufficient detail to perform a causality assessment. Conclusions: Overall, the number of deaths that we could reliably attribute to the prophylactic use of mefloquine is very low.